Hawker culture ethnocentrism: Building an integrative framework for consumer intention toward hawker centers - Gedecho, Ermias Kifle; Chua, Bee-Lia; Kim, Seongseop (Sam); Kim, Bona; Han, Heesup (Elsevier, 2023)
This study aimed to identify local diners' perceptions of Singaporean hawkers. It tested an integrated model incorporating place attachment, emotional solidarity, empowerment, and hawker culture ethnocentrism. Using a quantitative process, the dimensional structures of place attachment, emotional solidarity, and empowerment were ascertained. Four of six hypotheses incorporating structural relationships were supported. Interestingly, relationships between place attachment and emotional solidarity, between place attachment and empowerment, and between empowerment and hawker culture ethnocentrism were not signficant. Since this study applied concepts such as place attachment, emotional solidarity, empowerment, enthnocentrism to local street food consumption, this conceptual model is novel. The results of this study are expected to offer managerial implications to understand local patrons’ attitude and behavioral intentions toward hawker centers.